Answer:
-12y+48
Step-by-step explanation:
6(7-3y)+6(y+1)
42-18y+6y+6
-12y+42+6
-12y+48
The volume of the original prism is given by:
V1 = (1/2) * (b) * (h) * (H)
Where,
b: base of the triangle
h: height of the triangle
H: prism height
The volume of the prism with new dimensions is:
V2 = (1/2) * (3b) * (3h) * (3H)
Rewriting:
V2 = (3 * 3 * 3) * (1/2) * (b) * (h) * (H)
V2 = (27) * (1/2) * (b) * (h) * (H)
V2 = (27) * V1
Answer:
The relationship between the volumes of the two prisms is:
V2 = (27) * V1
Answer:
$8882.9
Step-by-step explanation:
A=p(1+(r/n))^nt
Given:P=7000, r=(3÷100%)=0.03 , n=2, t=8
A = 7000(1+(.03/2))^(2×8)
A = 7000 (1+0.015)^16
A = 7000 × 1.015^16
A = $8882.9
Step-by-step explanation:
a) Line AB ll DC
b) Line GH acts as a transversal.
c) <10 ; <12 , <9 ; <11
d) <8 = 180° - 120° = <u>60</u><u>°</u><u>(</u><u>Ans</u><u>)</u>
<6 = <u>120</u><u>°</u><u>(</u><u>Ans</u><u>)</u>
<5 = <u>60</u><u>°</u><u>(</u><u>Ans</u><u>)</u>
<4 = <u>60</u><u>°</u><u>(</u><u>Ans</u><u>)</u>
<3 = <u>120</u><u>°</u><u>(</u><u>Ans</u><u>)</u>
<2 = <u>120</u><u>°</u><u>(</u><u>Ans</u><u>)</u>
<1 = <u>60</u><u>°</u><u>(</u><u>Ans</u><u>)</u>